Guarding the switch: cultivating nationalism during the pullman strike - Rondinone, Troy (The Journal of the Gilded Age and Progressive Era, 2009)
The Pullman Strike of 1894 was a cataclysmic event for the nation. During its violent course, the print media provided an interpretive frame that portrayed the strike in large measure as an immigrant-inspired attack on American laws and democratic customs. Often characterizing the strikers as “foreigners” in the thrall of anarchist ideologies and a tyrannous labor chieftain, journalists painted a stark picture indeed. Employing framing theory, Gramsci's notion of hegemony, and recent insights on the ethnic quality of nationalism, this essay argues that newspapers and other major print periodicals significantly contributed to the formation of nationalist attitudes at a time when many Americans were deeply worried over the direction in which the country was headed. © 2009, Society for Historians of the Gilded Age and Progressive Era. All rights reserved.
Keywords: dept.his